Pathomorphological and microbiological analysis of an epoxy-treated bioprosthetic heart valve functioning for 25 years in a patient with rheumatic heart disease: a case report - A. E. Kostyunin; T. V. Glushkova; T. N. Akentyeva; E. A. Ovcharenko (Вестник трансплантологии и искусственных органов)
Bioprosthetic heart valves (BHVs) rarely last longer than 20 years due to the development of degenerative changes in their leaflets. We present a detailed pathomorphological description of KemCor, an epoxy-treated BHV that was removed from the mitral position 25 years after implantation. Literature review shows that this is the longest recorded lifespan of an epoxy-treated implant.